The care types choice in filial culture: A cross-sectional study of disabled elderly in China - Zang, Zheng (Frontiers in Public Health, 2022)
For the past few decades, studies of care types choice have been restricted to the scope of individual characteristics and health status. Meanwhile, the historiography of the research largely ignores the role of filial culture within China. This study sets out to examine the influence of the factors in the cultural context of filial piety on the choice of care types for older people with disability in China. According to the characteristics of filial culture, the factors influencing the choice of care type for the older people in China are summarized as family endowment and support. The study concludes that gender, residence, living alone or not, family income, real estate, pension and community service have momentous effects on the choice of care type of older people with disability; informal care has a substitutive effect on formal care. The research was based on cross-sectional data of CLHLS 2018 and utilized binary logistic regression analysis to compare the factors influencing the choice of old disabled people between formal and informal care. The study implies that in the context of filial culture, the older people's choice of care types is affected by family endowment and community service supply for the older people in China. In the background of filial culture, the government should give informal care official support such as cash and services, so as to change its attribute of private domain of it and enhance the quality of long-term care.